Pairwise Regularity and Normality Separation Axioms in C ̌ech Fuzzy Soft Bi-Closure Spaces - Hmood, Mohamad Th.; Majeed, R. N. (Iraqi Journal of Science, 2022)
In this paper, some new types of regularity axioms, namely pairwise quasi-regular, pairwise semi-regular, pairwise pseudo regular and pairwise regular are defined and studied in both ech fuzzy soft bi-closure spaces ( bicsp’s) and their induced fuzzy soft bitopological spaces. We also study the relationships between them. We show that in all these types of axioms, the hereditary property is satisfied under closed fs bi-csubsp of . Furthermore, we define some normality axioms, namely pairwise semi-normal, pairwise pseudo normal, pairwise normal and pairwise completely normal in both bicsp’s and their induced fuzzy soft bitopological spaces, as well as their basic properties and the relationships between them are studied.